The Matter of Piety Zoutleeuw's Church of Saint Leonard and Religious Material Culture in the Low Countries (c. 1450-1620) - Suykerbuyk, Ruben (Studies in Netherlandish Art and Cultural History, 2020)
The Matter of Piety provides the ﬁ rst in-depth study of Zoutleeuw's exceptionally well-preserved pilgrimage church in a comparative perspective, and revaluates religious art and material culture in Netherlandish piety from the late Middle Ages through the crisis of iconoclasm and the Reformation to Catholic restoration. Analyzing the changing functions, outlooks, and meanings of devotional objects - monumental sacrament houses, cult statues and altarpieces, and small votive oﬀ erings or relics - Ruben Suykerbuyk revises dominant narratives about Catholic culture and patronage in the Low Countries. Rather than being a paralyzing force, the Reformation incited engaged counterinitiatives, and the vitality of late medieval devotion served as the fertile ground from which the Counter-Reformation organically grew under Protestant impulses. Readership: All those interested in religious art, material culture, and patronage of the late medieval and early modern Low Countries, and anyone concerned with religious developments of the later Middle Ages, Reformation, and Counter-Reformation in Europe.